Wpływ czynników makroekonomicznych na kondycję finansową przedsiębiorstw w Polsce - przyczynek do dyskusji - Parkitna, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The influent factors on the financial form were qualified. The directions of the influence of external factors on financial conditions of the firm were showed. The results of the influence of external factors on financial conditions were identified. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 406-413